The Potential of ANGPTL8 Antagonism to Simultaneously Reduce Triglyceride and Increase HDL-Cholesterol Plasma Levels - Zhang, Ren (Frontiers in Cardiovascular Medicine, 2021)
Elevated triglyceride (TG) and reduced high-density lipoprotein-cholesterol (HDL-C) plasma levels are risk factors for atherosclerosis and cardiovascular disease. Therefore, a drug that simultaneously reduces TG and increases HDL-C plasma levels has the potential to prevent and treat these diseases. Angiopoietin-like 3 (ANGPTL3) regulates plasma TG and HDL-C levels by inhibiting lipoprotein lipase (LPL) and endothelial lipase (EL), respectively. ANGPTL3 inhibition of LPL requires complex formation with ANGPTL8, which is not required for its inhibition of EL. Therefore, the entire pool of plasma ANGPTL3 can be classified as ANGPTL8-associated ANGPTL3 and ANGPTL8-free ANGPTL3, where the former inhibits LPL and the latter inhibits EL. ANGPTL8 antibodies or inhibitors that block its interactions with ANGPTL3 can disrupt or preclude the ANGPTL3-8 complex formation, resulting in fewer ANGPTL3-8 complexes (reduced LPL inhibition), but more free ANGPTL3 (enhanced EL inhibition). Therefore, ANGPTL8 antagonism increases LPL activity while decreasing EL activity, thus leading to reduced plasma TG while simultaneously increasing HDL-C levels. In humans, carriers of ANGPTL8 truncating variants consistently have lower TG but higher HDL-C levels, supporting this hypothesis.